Hybrid Emission Modeling of GRB 221009A: Shedding Light on TeV Emission Origins in Long GRBs - Hebzibha Isravel; Damien Bégué; Asaf Pe’er (The Astrophysical Journal, 2023)
Observations of long-duration gamma-ray bursts (GRBs) with TeV emission during their afterglow have been on the rise. Recently, GRB 221009A, the most energetic GRB ever observed, was detected by the Large High Altitude Air Shower Observatory experiment in the energy band 0.2–7 TeV. Here, we interpret its afterglow in the context of a hybrid model in which the TeV spectral component is explained by the proton-synchrotron process while the low-energy emission from optical to X-ray is due to synchrotron radiation from electrons. We constrained the model parameters using the observed optical, X-ray, and TeV data. By comparing the parameters of this burst and of GRB 190114C, we deduce that the VHE emission at energies ≥1 TeV in the GRB afterglow requires large explosion kinetic energy, E ≳ 10 ^54 erg and a reasonable circumburst density, n ≳ 10 cm ^−3 . This results in a small injection fraction of particles accelerated to a power law, ∼10 ^−2 . A significant fraction of shock energy must be allocated to a near equipartition magnetic field, ϵ _B ∼ 10 ^−1 , while electrons should only carry a small fraction of this energy, ϵ _e ∼ 10 ^−3 . Under these conditions required for a proton-synchrotron model, namely ϵ _B ≫ ϵ _e , the SSC component is substantially subdominant over proton-synchrotron as a source of TeV photons. These results lead us to suggest that proton-synchrotron process is a strong contender for the radiative mechanisms explaining GRB afterglows in the TeV band.